New Insights into Literature and Catholicism in the 19th and 20th Centuries - Rowan, Paul, 1968-; Torevell, David (Cambridge Scholars Publishing, 2021)
This volume deepens thinking and research about literature and Catholicism in the 19th and 20th centuries. It develops the understanding that a number of acclaimed literary texts have reflected, in imaginative and memorable ways, a distinctive Catholic sensibility, identity and philosophy of life, and, in so doing, have shed light on profound spiritual experiences in a variety of fictional settings.